REVITALISASI KEARIFAN LOKAL SUNDA - Sumardjo, Jakob (Jurnal Budaya Nusantara, 2018)
In Sundanese culture, local wisdom is the middle sineger (sineger tengah) or middle siger (siger tengah) a middleground that is moderate. The excavation of local Sundanese wisdom means finding a rational pattern or basicphilosophy that is suitable for living in this area. In other areas where the situation is similar it is possible to find abasic philosophy which is more or less the same. Foreign local wisdom which enters the local wisdom of Sundanese tendsto conform not the other way around. Times will always change but Sundanese become another Sundanese of its ownkinds. The outward form can change, but the structure and pattern of building the meaning of life tend to remain workgenetically unnoticed because since childhood has been investigated by the older generation in the same pattern. Therevitalization of Sundanese culture is necessary or not depending on its actuality to solve the present problems.